2023
DOI: 10.3390/pr11072116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Motor Installation Heights on the Performance of an Isolated Centrifugal Fan

Abstract: For this paper, an investigation into the differences in the aerodynamic performance of fans caused by installation heights was conducted using computational fluid simulation. The predictions presented in this paper are in great agreement with the experimental data. The results show that a vortex is observable on the side of the motor, as it first accelerates and then obviously decelerates while passing through the impeller inlet to the front of the blade passage. Higher motor installation heights result in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Computational fluid dynamics (CFD) is widely utilized for analyzing the flow field and optimizing the performance of centrifugal fans [11,12]. An interesting finding revealed that the dominant patterns of jet-wake flow were caused by vortex and blade channel blockage, resulting in high velocities on the pressure side of the blade [13].…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) is widely utilized for analyzing the flow field and optimizing the performance of centrifugal fans [11,12]. An interesting finding revealed that the dominant patterns of jet-wake flow were caused by vortex and blade channel blockage, resulting in high velocities on the pressure side of the blade [13].…”
Section: Introductionmentioning
confidence: 99%